2016
DOI: 10.1128/genomea.01286-16
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Three Clinical Isolates of Tannerella forsythia Isolated from Subgingival Plaque from Periodontitis Patients in the United States

Abstract: We report the genome sequences of three clinical isolates of Tannerella forsythia from the subgingival plaque of periodontitis patients attending clinics at the School of Dental Medicine, University at Buffalo. The availability of these genome sequences will aid the understanding of the pathogenesis of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
(16 reference statements)
1
10
0
Order By: Relevance
“…The amplification and sequencing of various NulO biosynthesis genes indicated that UB4 possesses the same Leg biosynthesis gene locus as strain FDC 92A2 (Supplementary Figure 4). This was confirmed by an alignment of the FDC 92A2 genome with the recently published genome of strain UB4, which revealed a nucleotide identity of 99.8% in this cluster (Stafford et al in preparation). The aminotransferase genes pseC and legC were selected as targets for gene knockouts in the ATCC 43037 type strain and UB4, respectively.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The amplification and sequencing of various NulO biosynthesis genes indicated that UB4 possesses the same Leg biosynthesis gene locus as strain FDC 92A2 (Supplementary Figure 4). This was confirmed by an alignment of the FDC 92A2 genome with the recently published genome of strain UB4, which revealed a nucleotide identity of 99.8% in this cluster (Stafford et al in preparation). The aminotransferase genes pseC and legC were selected as targets for gene knockouts in the ATCC 43037 type strain and UB4, respectively.…”
Section: Resultssupporting
confidence: 63%
“…A homology search of C. jejuni NulO biosynthesis amino acid sequences against the genomes of strains FDC 92A2 (Genbank CP003191) and UB4 (Stafford et al in preparation) revealed major differences with respect to the genome of strain ATCC 43037. The putative flippase gene (Tanf_01180/BFO_1075) is identical in FDC 92A2, UB4 and the type strain along almost its entire length, however, alignment breaks down over the last 30 base pairs (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Mutants of T. forsythia ATCC 43037 (JUET00000000) and T. forsythia UB4 (FMMN01000000) with characterized defects in their cell surface protein glycosylation, affecting the terminal Pse (ATCC 43037) or Leg (UB4) residue, were available in our laboratory from a previous study . Briefly, T. forsythia ATCC 43037 ∆ pseC (coding for a dedicated aminotransferase from the Pse biosynthesis pathway) and T. forsythia UB4 ∆ legC (coding for a dedicated aminotransferase from the Leg biosynthesis pathway) mutants were constructed by chromosomal insertion of a gene knockout cassette consisting of an erythromycin resistance gene flanked by homologous upstream and downstream regions, ~1000 bp, each.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, T. forsythia wild‐type strains ATCC 43037 (type strain, American Type Culture Collection, Manassas, VA) and T. forsythia UB4 as well as defined mutants thereof were cultured anaerobically in brain‐heart infusion (BHI) broth (Oxoid, Basingstoke, UK) and BHI agar plates, supplemented with N ‐acetylmuramic acid and horse serum as described previously . Mutants with characterized defects in protein glycosylation included T. forsythia ATCC 43037 ∆ pseC (deficient in Pse), T. forsythia ATCC 43037 ∆wecC (deficient in a trisaccharide glycan branch including Pse) and T. forsythia UB4 ∆ legC (deficient in Leg).…”
Section: Methodsmentioning
confidence: 99%